Strategi Mewujudkan Harmoni Sosial Pada Masyarakat Beragama Islam dan Kristen di Kecamatan Bukit Malintang Kabupaten Mandailing Natal (Tahun 2024) - Ester Harianja; Harisan Boni Firmando; Masniar Herawati Sitorus; Maringan Sinambela; Rusmauli Simbolon (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2024)
This research aims to determine the strategy for realizing social harmony in Islamic and Christian communities in Bukit Malintang District, Mandailing Natal Regency, knowing the forms and forms of social harmony and the efforts made to create social harmony in Islamic and Christian communities in Bukit Malintang District, Mandailing Regency. Christmas 2024. This research uses qualitative research methods. Data collection in this research uses observation, interviews and documentation techniques. Social harmony is compatibility, suitability, balance and justice which provides a sense of security, peace and prosperity to all mankind. Broadly speaking, it means the existence of brotherhood and togetherness between religious communities even though they are different in terms of ethnicity, race and class. The results of this research show that in the villages of Promisematogu and Lambou Dahlul Ihsan, each religion teaches to live in peace and tranquility. The importance of awareness among the adherents of each religion makes it very easy to establish social harmony in society. So that people can live in peace, help each other, respect each other, in everyday life. Religious figures also often emphasize the importance of tolerance as a basis for peaceful coexistence. By implementing the Dalihan Na Tolu system, the kinship system has an important meaning that looks at the relationship between Islamic and Christian communities in the kinship system incorporated in Dalian Na Tolu, overcoming relationships that are built on the basis of inter-religious brotherhood.